ANALISIS RASIO LAPORAN KEUANGAN SEBAGAI PENGUKURAN KINERJA PEMERINTAH KABUPATEN GARUT TAHUN 2020-2021 - Risca Novalia; Eni Duwita Sigalingging (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Since the implementation of regional autonomy, regional governments have had control over financing and implementing regional interests in accordance with the resources and potential of their regions. Regional governments must become independent in managing and improving their financial performance to reduce their dependence on the central government. Anggaran Pendapatan dan Belanja Daerah (APBD) is a funding for regional governments in running the government system. Regional financial management is based on the principles of transparency, accountability and value for money so that the government is responsible for reporting the results of APBD management. Laporan Keuangan Pemerintah Daerah (LKPD) is a tool for controlling and evaluating their financial performance for the community. This research aims to determine the financial performance of Pemerintah Kabupaten Garut in 2020 and 2021. Performance assessment is carried out by analyzing the financial reports in the Laporan Realisasi Anggaran, by measuring financial ratios such as independence ratio, effectiveness ratio and efficiency ratio. Based on the research conducted, the results obtained were that the independence ratio of Pemerintah Kabupaten Garut had a Very Low level of financial capability and an Instructive relationship pattern. Meanwhile, the PAD effectiveness ratio calculation is at the Very Effective level and the PAD efficiency ratio is at the Inefficient level.